Studies in natural products chemistry : Vol. 49 - Rahman, Atta-ur-, 1942- (Amsterdam, Netherlands : Elsevier, 2016)
Studies in Natural Products Chemistry: Bioactive Natural Products (Part XIII) is the latest in a series that covers the synthesis or testing and recording of the medicinal properties of natural products, providing cutting-edge accounts of the fascinating developments in the isolation, structure elucidation, synthesis, biosynthesis, and pharmacology of a diverse array of bioactive natural products. Natural products in the plant and animal kingdom offer a huge diversity of chemical structures that are the result of biosynthetic processes that have been modulated over the millennia through genetic effects. With the rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to quickly isolate and determine the structures and biological activity of natural products, thus opening up exciting opportunities in the field of new drug development to the pharmaceutical industry.
Antirespiratory Syncytial Virus ActivityAntiviral Activity Against Other Viruses; OTHER ACTIVITIES OF/ IARYLHEPTANOIDS; MOLECULAR PHARMACOLOGICAL/ VALUATION BY TRANSLATION/ ROFILING; CONCLUSION; ABBREVIATIONS; REFERENCES; 5 -- Bioactive Secondary Metabolites From Endophytic Fungi: A Review of Biotechnological Production and Their Potential Applications ; INTRODUCTION; ENDOPHYTES AND THEIR DIVERSITY; ENDOPHYTE-HOST ASSOCIATION; ENDOPHYTES FOR BIOACTIVE/ ETABOLITE PRODUCTION; Selection of Plant for Novel Endophytes.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed September 19, 2016).
Keywords: Bioorganic chemistry; Bioactive compounds; Natural products; SCIENCE -- Life Sciences -- Biochemistry; Bioactive compounds; Bioorganic chemistry; Natural products; Chemistry, Organic; Electronic books